جدید اردو نظم میں سماجی شعور - Khayaban; ڈاکٹر انتل ضیا; نوشین مہمند; ڈاکٹر زینب شاہ (Khayaban - خیابان, 2026)
This article explains how modern Urdu nazm shows social awareness by discussing issues like class differences, political injustice, human freedom, and social change. The Progressive Writers’ Movement greatly influenced this form of poetry and turned it into a voice of resistance and social criticism. By looking at the works of Iqbal, Faiz, Jalib, Faraz, Sahir, and others, the study shows how Urdu poetry represents people’s struggles and encourages social and intellectual awakening. The article concludes that modern Urdu nazm is not just poetry, but also a reflection of the social and political conditions of its time.